Analysis of Faulting and Earthquake Processes: from Laboratory Experiments to Crustal-Scale Investigations - Chang, Jefferson C. (My University, 2017)
This dissertation encompasses a wide range of scale that investigates the tectonic processes in the crust with respect to faulting and earthquakes. of tectonic and earthquake processes in the crust. I present in four chapters: (1) rotary shear experiments in the laboratory that simulate earthquakes of MW4-8, which I define the Coulomb Energy Density as a new unit to quantify seismic energy that is proportional to slip-distance of an earthquake patch; (2) a 3D seismic tomography to delineate the basin thickness underlying Tanghsan, China, which is a densely populated city with a history of catastrophic seismicity; (3) seismic observations from Oklahoma 2010-2017, where a sudden increase from less than three felt earthquakes per year prior to 2010 to over 900 felt events in 2015, points to the involvement of wastewater disposal wells and hydraulic fracturing stimulations as likely triggers; and (4) I created a fast and accurate method of calculating gravity effects of mass, which was used to model crustal structures to investigate Oklahoma seismicity.
Keywords: earthquake processes; Oklahoma seismicity; Tangshan, China; gravity modeling